2020
DOI: 10.1108/ejmbe-09-2019-0158
|View full text |Cite
|
Sign up to set email alerts
|

Market structure, institutional quality and bank capital ratios: evidence from developing countries

Abstract: PurposeThis paper investigates the role of market structure and institutional quality in determining bank capital ratios in developing economies.Design/methodology/approachThe generalised methods of moment technique is used to control for auto-correlation and endogeneity in a sample of 79 publicly listed commercial banks. The study period is between 2000 and 2016.FindingsResults show that market structure (proxied with bank competition) as well as institutional quality (regulatory quality) lowers bank capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Although numerous investigations were conducted to determine the effect of institutional quality on the economic and financial development of a country, the impact of institutional quality on banking stability is under-researched (Canh et al , 2021; Uddin et al , 2020). Furthermore, Chan et al (2015) and Etudaiye-Muhtar and Abdul-Baki (2020) suggest that market structure and institutional quality may jointly affect the banking system in developing countries. Therefore, this study examines the market structure and institutional quality's joint effect on bank stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous investigations were conducted to determine the effect of institutional quality on the economic and financial development of a country, the impact of institutional quality on banking stability is under-researched (Canh et al , 2021; Uddin et al , 2020). Furthermore, Chan et al (2015) and Etudaiye-Muhtar and Abdul-Baki (2020) suggest that market structure and institutional quality may jointly affect the banking system in developing countries. Therefore, this study examines the market structure and institutional quality's joint effect on bank stability.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies on capital structure in the banking sector, researchers find that the level of profitability has a negative effect on the capital structure (Al-Hunnayan, 2020;Ghosh & Chatterjee, 2018;Guizani & Ajmi, 2021;Kahya et al, 2020;Khan et al, 2020). However, several studies have found that the profitability of banking companies has a positive and significant effect on their debt structure (Etudaiye-Muhtar& Abdul-Baki, 2020). The results of this study indicate that international banks are more careful in maintaining their debt ratios, as debt to banks is a 'commodity' that is used to earn profits.…”
Section: Hypothesis Testing and Discussionmentioning
confidence: 66%
“…For example, from the trade-off theory point of view, the company's profitability has a positive effect on the company's debt structure due to increased tax benefits. In other words, the more increasing the company's profitability, the more likely the company is in debt (El-Sayed Ebaid, 2009;Etudaiye-Muhtar & Abdul-Baki, 2020;Kraus & Litzenberger, 1973;Rani, Yadav, & Tripathy, 2019).…”
Section: Determinants Of Capital Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The wave of failures among Russian banks can have dramatic social consequences and be detrimental for the stability of the financial system as a whole (Fung a cov a and Weill, 2013). However, at the same time, the banking concentration can strengthen the financial system because bigger banks have better chances to diversify their risk, and it is easier to monitor a reduced number of banks (Etudaiye-Muhtar and Abdul-Baki, 2021). Although there are a number of papers about bankruptcy prediction in Russian banks, most of them are based on outdated data, so that there is room for new evidence.…”
Section: Introductionmentioning
confidence: 99%